Prx1 cell subpopulations identified in various tissues with diverse quiescence and activation ability following fracture and BMP2 stimulation - Liu, Yu; Ilinski, Adrian; Gerstenfeld, Louis C.; Bragdon, Beth (Frontiers in Physiology, 2023)
The expression of Prx1 has been used as a marker to define the skeletal stem cells (SSCs) populations found within the bone marrow and periosteum that contribute to bone regeneration. However, Prx1 expressing SSCs (Prx1-SSCs) are not restricted to the bone compartments, but are also located within the muscle and able to contribute to ectopic bone formation. Little is known however, about the mechanism(s) regulating Prx1-SSCs that reside in muscle and how they participate in bone regeneration. This study compared both the intrinsic and extrinsic factors of the periosteum and muscle derived Prx1-SSCs and analyzed their regulatory mechanisms of activation, proliferation, and skeletal differentiation. There was considerable transcriptomic heterogeneity in the Prx1-SSCs found in muscle or the periosteum however in vitro cells from both tissues showed tri-lineage (adipose, cartilage and bone) differentiation. At homeostasis, periosteal-derived Prx1 cells were proliferative and low levels of BMP2 were able to promote their differentiation, while the muscle-derived Prx1 cells were quiescent and refractory to comparable levels of BMP2 that promoted periosteal cell differentiation. The transplantation of Prx1-SCC from muscle and periosteum into either the same site from which they were isolated, or their reciprocal sites showed that periosteal cell transplanted onto the surface of bone tissues differentiated into bone and cartilage cells but was incapable of similar differentiation when transplanted into muscle. Prx1-SSCs from the muscle showed no ability to differentiate at either site of transplantation. Both fracture and ten times the BMP2 dose was needed to promote muscle-derived cells to rapidly enter the cell cycle as well as undergo skeletal cell differentiation. This study elucidates the diversity of the Prx1-SSC population showing that cells within different tissue sites are intrinsically different. While muscle tissue must have factors that promote Prx1-SSC to remain quiescent, either bone injury or high levels of BMP2 can activate these cells to both proliferate and undergo skeletal cell differentiation. Finally, these studies raise the possibility that muscle SSCs are potential target for skeletal repair and bone diseases.